2013
DOI: 10.1111/den.12030
|View full text |Cite
|
Sign up to set email alerts
|

Relation between bile acid reflux into the stomach and the risk of atrophic gastritis and intestinal metaplasia: A multicenter study of 2283 cases

Abstract: High concentrations of bile acid seem to be associated with an elevated risk of intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 18 publications
0
68
0
6
Order By: Relevance
“…In line with Rutledge et al's findings, no EGJ function and motility abnormalities were observed after OGB. In addition, for the first time we documented a drastic reduction not only in esophageal acid exposure time but also in all kinds of refluxes (acidic, weakly acidic, and (3)(4)(5) .000 26 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 38 .000 Recumbent 9 (2-16) 0 (0-2) .000 7 (4-9) 15 (10)(11)(12)(13)(14)(15)(16)(17) .000 Acid reflux pattern at MII Total 32 (15-50) 3 (3)(4)(5)(6) .000 12 (9)(10)(11)(12)(13)(14) 16 (9--18) .000 Upright 27 (13-37) 3 (3)(4) .008 9 (8-10) 13 (7)(8)(9)(10)(11)(12)(13)(14)…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In line with Rutledge et al's findings, no EGJ function and motility abnormalities were observed after OGB. In addition, for the first time we documented a drastic reduction not only in esophageal acid exposure time but also in all kinds of refluxes (acidic, weakly acidic, and (3)(4)(5) .000 26 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 38 .000 Recumbent 9 (2-16) 0 (0-2) .000 7 (4-9) 15 (10)(11)(12)(13)(14)(15)(16)(17) .000 Acid reflux pattern at MII Total 32 (15-50) 3 (3)(4)(5)(6) .000 12 (9)(10)(11)(12)(13)(14) 16 (9--18) .000 Upright 27 (13-37) 3 (3)(4) .008 9 (8-10) 13 (7)(8)(9)(10)(11)(12)(13)(14)…”
Section: Discussionmentioning
confidence: 71%
“…Although duodenogastric bile reflux is a physiologic phenomenon [19,20], excessive duodenogastric biliary reflux can lead to intestinal metaplasia, esophageal mucosal damage, symptomatic gastritis/ esophagitis, Barrett's esophagus, and gastric/esophageal cancer [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Причём в одних данных не найдено связи её развития с хе-ликобактерной инфекцией [6], в других ра-ботах показано, что риск развития интести-нальной метаплазии при ДГР повышается при наличии хеликобактерной инфекции, а при её отсутствии ДГР не приводит к дан-ным морфологическим изменениям [7].…”
Section: Morphological Characteristics Of Reflux Gastritisunclassified
“…В отношении гландулярной атрофии в наибольшем количестве встретившихся нам работ указано, что рефлюкс-гастрит нельзя считать фактором риска её развития [6]. Однако в других работах было показа-но, что ДГР не только является причиной развития атрофии СОЖ, но и по-разному воздействует на развитие атрофии на раз-ных уровнях желудка.…”
Section: Morphological Characteristics Of Reflux Gastritisunclassified
See 1 more Smart Citation